The dilemma of antibiotic susceptibility and clinical decision-making in a multi-drug-resistant Pseudomonas aeruginosa bloodstream infection - Long Chen; Xingyi Qu; Xingyi Qu; Jingqian Su; Haijun Yao; Qiang Yuan; Yu Wang; Nanyang Li; Gang Wu; Xiaofen Liu; Jin Hu; Jing Zhang; et al. (Frontiers Media S.A., 2023)
Objective: How to choose the appropriate antibiotics and dosage has always been a difficult issue during the treatment of multi-drug-resistant bacterial infections. Our study aims to resolve this difficulty by introducing our multi-disciplinary treatment (MDT) clinical decision-making scheme based on rigorous interpretation of antibiotic susceptibility tests and precise therapeutic drug monitoring (TDM)-guided dosage adjustment.Method: The treatment course of an elderly patient who developed a multi-drug-resistant Pseudomonas aeruginosa (MDRPA) bloodstream infection from a brain abscess was presented.Results: In the treatment process, ceftazidime-avibactam (CAZ-AVI) was used empirically for treating the infection and clinical symptoms improved. However, the follow-up bacterial susceptibility test showed that the bacteria were resistant to CAZ-AVI. Considering the low fault tolerance of clinical therapy, the treatment was switched to a 1 mg/kg maintenance dose of susceptible polymyxin B, and TDM showed that the AUC24h, ss of 65.5 mgh/L had been achieved. However, clinical symptoms were not improved after 6 days of treatment. Facing the complicated situation, the cooperation of physicians, clinical pharmacologists, and microbiologists was applied, and the treatment finally succeeded with the pathogen eradicated when polymyxin B dose was increased to 1.4 mg/kg, with the AUC24h, ss of 98.6 mgh/L.Conclusion: MDT collaboration on the premise of scientific and standardized drug management is helpful for the recovery process in patients. The empirical judgment of doctors, the medication recommendations from experts in the field of TDM and pharmacokinetics/pharmacodynamics, and the drug susceptibility results provided by the clinical microbiology laboratory all provide the direction of treatment.